Al-Ghazali Dalam Keperilakuan Manajemen Keuangan: Al-Ghazali Dalam Keperilakuan Manajemen Keuangan - Indra Lukmana Putra (Edusifa: Jurnal Pendidikan Islam, 2025)
This reseach about values of Al-Ghazali Islamic Behaviour Ethics for making decision on Finance Management. Some Phenomena violations of ethical practices fraud on financial management. assumption is that the degradation of ethical behavior is due to a lack of values religion in behavior in financial management loss of function in distinguishing between what is good and what is wrong the bad one. This research using the library research method aims to raise the value of religiosity, especially according to Al-Ghazali in his book Mizan al-'Amal or Al-Mizan, in the context about financial management in decision making. Behavioural finance how influence of psychology of integrity can be expanded in terms of making decision and meaning with the mujahadah component in Al-Mizan, that integrity referred to here is trying to avoid bad trait that are prohibited in Islam and this leads to compliance with regulations and avoiding bad actions like fraud management.